KEEFEKTIFAN MODEL PROJECT BASED LEARNING (PjBL) BERBASIS YOUTUBE PADA TEMA 2 UDARA BERSIH BAGI KESEHATAN SUB TEMA 1 CARA TUBUH MENGOLAH UDARA BERSIH UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS V SDN SUNGGINGWARNO 01 - Andhika Wahyu Pratomo; Fine Reffiane; Moh Aniq Khairul Basyar (STKIP Subang, 2023)
This qualitative research with a case study approach was used to provide insight into real world conditions and realities, especially the strategies used by teachers to overcome bullying behavior at SD Negeri Sunggingwarno 01 Pati Regency. In this case, first, researchers will conduct interviews with teachers as informants, because teachers are coaches, and create a supportive and comprehensive social context that does not tolerate aggressive and violent behavior at school by students. This research aims to determine the effectiveness of the Project based Learning model on students' learning outcomes on theme 2 clean air for health, subtheme 1 how the body manages clean air. This research was applied to class V students at SDN Sunggingwarno 01. The results of this research were that there was an influence of using the YouTube-based PJBL model through the use of teaching aids on students' learning outcomes. Thus, the PjBL model can be used by teachers as an alternative learning method to improve student learning outcomes.